Cloning and nucleotide sequence of the gene encoding the 136-kilodalton surface protein (muramidase-released protein) of Streptococcus suis type 2. - Smith, H E (1992)
We cloned and sequenced the gene encoding the muramidase-released protein (MRP) of a pathogenic Streptococcus suis type 2 strain to determine whether its amino acid sequence resembles that of proteins with known functions and to determine its function in virulence. The complete nucleotide sequence composing the gene and the regions flanking it was determined. The deduced amino acid sequence revealed the presence of a signal peptide at the N terminus and a cell envelope anchor at the C terminus, both of which resembled similar regions in several other surface proteins from gram-positive bacteria. The processed form of MRP has a length of 1,209 amino acids and a calculated molecular weight of 131,094. A highly repetitive region preceded the envelope anchor. The repeated units were preceded by a proline-rich stretch of amino acids (26 of 86). No overall homologies were observed between the amino acid sequence of MRP and protein sequences in the EMBL data bank. A particular region within the amino acid sequence, however, showed some similarity with the fibronectin-binding protein of Staphylococcus aureus. Binding of MRP to human fibronectin, however, could not be confirmed.